Third-Grade Student Use of a Computer Program for Keyboarding: Development of Keyboarding Skills, Student Perceptions Toward Keyboarding, and Use of Multiple Intelligences - Bruns, Vicki (My University, 2007)
This thesis is comprised of two primary sections, an action research proposal and a journal ready article. The journal ready article presents the findings of the action research. Based on direct classroom observations, discussions with elementary school teachers, and a review of the literature, I have discovered when a lack of keyboarding instruction is provided, students often use a "hunt and peck" method of typing. The purpose of the action research study was to describe the influence of a software program, Type to Learn 3, on third-grade student keyboarding skills and student perceptions of keyboarding. In addition, students' selection of keyboarding activities from the software program and the students' intelligences, were examined to identify possible relationships between them. As delineated in the action research proposal, a class of 19 third-grade students used the keyboarding software program, Type to Learn 3, for 45 minutes each school day during a 3-week period. As described in the journal ready article, data were collected from keyboarding skills tests, attitude surveys, student interviews, progress reports available through the computer program, and a keyboarding skills checklist. The results of the study showed that students' keyboarding skills improved in both speed and accuracy, and students' perceptions toward keyboarding were positive. Results were inconclusive when trying to determine whether students' selection of keyboarding activities related to students' multiple intelligences. The findings of this study were communicated to the learning community through a PowerPoint slide show presentation during a faculty "Share Fair." Feedback from the presentation supported revisions in next year's class schedules to provide keyboarding instruction to third-grade students.
Keywords: Type to Learn 3; keyboarding skills; student perceptions